Physicochemical and Functional Properties of Nano-Chitosan Derived from Green Mussel (Perna viridis) Shells - Firmani, Ummul; Safitri, Nur Maulida; Rahim, Andi Rahmad (Department of Aquaculture, 2025)
Increasing stocking density in catfish cultivation is part of efforts to increase production to meet catfish needs nationally and internationally. The obstacles faced by household Green mussels (Perna viridis) are a major fishery commodity in Indonesia, producing substantial shell waste. Green mussel shell waste can be used as shrimp feed because of its high calcium content. Nano-chitosan, derived from chitin extracted from green mussel shells, offers enhanced bioavailability and functional properties, making it a promising additive for feed applications. Nano chitosan has the advantage of being biocompatible, biodegradable, and non-toxic. The goal of this study is to create a nano chitosan extract from green mussel shells. Green mussel shells are extracted during the stages of deproteination, demineralization, and deacetylation. The obtained chitosan extract is then combined with Sodium Tripolyphosphate (NaTTP) to yield nano chitosan particles. The nano chitosan particles were then measured and analyzed for the compounds they contained. The extracted chitosan appeared white, with a yield of 71%, which aligns with previous studies on shell-derived chitosan. FTIR analysis confirmed the presence of characteristic chitosan functional groups, including C=O and O-H, at 343 nm. This study successfully synthesized nano-chitosan from green mussel shells that have biocompatibility and high calcium content.